Protein cargo in extracellular vesicles as the key mediator in the progression of cancer - Hánělová, Klára; Raudenská, Martina; Masařík, Michal; Balvan, Jan (Cell communication and signaling, 2024)
Exosomes are small vesicles of endosomal origin that are released by almost all cell types, even those that are pathologically altered. Exosomes widely participate in cell-to-cell communication via transferring cargo, including nucleic acids, proteins, and other metabolites, into recipient cells. Tumour-derived exosomes (TDEs) participate in many important molecular pathways and affect various hallmarks of cancer, including fibroblasts activation, modification of the tumour microenvironment (TME), modulation of immune responses, angiogenesis promotion, setting the pre-metastatic niche, enhancing metastatic potential, and affecting therapy sensitivity and resistance. The unique exosome biogenesis, composition, nontoxicity, and ability to target specific tumour cells bring up their use as promising drug carriers and cancer biomarkers. In this review, we focus on the role of exosomes, with an emphasis on their protein cargo, in the key mechanisms promoting cancer progression. We also briefly summarise the mechanism of exosome biogenesis, its structure, protein composition, and potential as a signalling hub in both normal and pathological conditions. Video Abstract.
Keywords: nádorové mikroprostředí; Extracellular Vesicles; nádory; Exosomes; lidé; Signal Transduction; signální transdukce; Neoplasms; Tumor Microenvironment; Cell Communication; mezibuněčná komunikace; exozómy; extracelulární vezikuly; Humans